Group Absence Behavior and Standards: A Multilevel Analysis - Markham, Steven E.; McKee, Gail H. (Academy of Management Journal, 1995)
This research measured Nicholson and John's concept of the salience of absence climate in terms of absence standards for supervisory groups. Within and between analysis (WABA) was used to determine whether these standards showed group-level effects on absence behavior. With gender controlled, supervisory groups that had perceptions of high external management standards for absence and high internal personal standards also had low levels of absence. Furthermore, the internal personal standards of supervisors significantly predicted absence for entire groups. No plant-level effects were detected.